2013
DOI: 10.1097/bpo.0b013e31827b7b0c
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Nonaccidental Injury

Abstract: Level III-retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Moreover, the lengthier the orthopedist's professional experience, the higher the likelihood of referral, namely, each additional year in the profession increased the likelihood of referral by 8%. These findings contrast with a previous study by Tenenbaum and associates, 8 who found that less-experienced physicians demonstrated more awareness and tendency to further investigate cases with suspected NAT than experienced physicians. Notably, in the present study, no association was found between the treating orthopedist's nationality and the likelihood of referring a child with a femur fracture to a social worker.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Moreover, the lengthier the orthopedist's professional experience, the higher the likelihood of referral, namely, each additional year in the profession increased the likelihood of referral by 8%. These findings contrast with a previous study by Tenenbaum and associates, 8 who found that less-experienced physicians demonstrated more awareness and tendency to further investigate cases with suspected NAT than experienced physicians. Notably, in the present study, no association was found between the treating orthopedist's nationality and the likelihood of referring a child with a femur fracture to a social worker.…”
Section: Discussioncontrasting
confidence: 99%
“…8,17 Thus, one study found that although the American Academy of Orthopedic Surgeons issued clinical practice guidelines recommending NAT evaluation for all patients younger than 36 months, only 48% of this population was indeed evaluated. 17 Moreover, a study by Tenenbaum et al 8 found that although experienced physicians demonstrated higher levels of knowledge than less-experienced physicians, the latter demonstrated more awareness and tendency to further investigate cases with suspected NAT.…”
mentioning
confidence: 99%
See 3 more Smart Citations